Comprehension of Online Educational Material Regarding Orofacial Clefts. (October 2019) - Jodeh, Diana S.; Pringle, Aleshia J.; Rottgers, S. Alex
Background: Cleft lip and palate are among the common birth defects in the United States. Management is complex and may be difficult for parents and patients to understand. The goal of this study was to evaluate the readability of online educational material provided by the American Society of Plastic Surgeons (ASPS) and the American Cleft Palate-Craniofacial Association (ACPA) websites regarding cleft lip and palate and to assess parents' comprehension. Methods: Parents of children younger than 10 years of age presenting to the plastic and reconstructive surgery clinic at Johns Hopkins All Children's Hospital for conditions other than cleft lip and palate were recruited for participation. Parents were given the literature published on the ASPS and ACPA web sites to review and were asked to complete a 5-question test specifically targeted to the content of the passage they reviewed. We tested the readability of the 2 online passages using Readability Studio software (Oleander Software Solutions Ltd). Results: Sixty parents completed the study. Across all groups, the mean score was 4.35 of a possible 5. The mean score was 4.4 for the ASPS web site and 4.29 for the ACPA web site. Fifty-three percent of participants answered all questions correctly. No significant difference in scores was noted between web sites ( P = .48). Conclusions: Despite containing content of varying reading-level difficulty, the literature posted on the ACPA and ASPS web sites concerning cleft lip and palate conveyed information equally well to the target parent demographic with high levels of comprehension.